2010
DOI: 10.1063/1.3377921
|View full text |Cite
|
Sign up to set email alerts
|

Study of electric characteristics and diffusion effects of 2-methyl-9,10-di(2-naphthyl)anthracene doped with cesium fluoride by admittance spectroscopy

Abstract: Study of electrical characterization of 2-methyl-9, 10 -d i (2-naphthyl)anthracene doped with tungsten oxide as hole-transport layer Appl. Phys. Lett. 95, 033501 (2009); 10.1063/1.3173824Studies of the degradation mechanism of organic light-emitting diodes based on tris (8-quinolinolate)aluminum Alq and 2-tert-butyl-9,10-di(2-naphthyl)anthracene TBADN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…To investigate the hole-injection barrier at the anode/HIL interface of the studied devices, we made devices B(5), B(10), and B(20) for IS measurement. Actually, IS measurement is a very useful method to study electrical properties of electronic devices. The details of the IS measurement for the study of hole-injection barrier have been reported by Hsieh et al , Considering the energy barrier between the Alq layer and the aluminum cathode, as well as the very low oscillation level, these devices can be treated as hole-only devices. , Moreover, each layer in the devices can be treated as an RC element according to the IS theory . However, because the parallel resistance of 60 nm Alq layer is much larger than that of the doped CBP layer in the devices, the RC element of the CBP layer can be treated as only a capacitor.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the hole-injection barrier at the anode/HIL interface of the studied devices, we made devices B(5), B(10), and B(20) for IS measurement. Actually, IS measurement is a very useful method to study electrical properties of electronic devices. The details of the IS measurement for the study of hole-injection barrier have been reported by Hsieh et al , Considering the energy barrier between the Alq layer and the aluminum cathode, as well as the very low oscillation level, these devices can be treated as hole-only devices. , Moreover, each layer in the devices can be treated as an RC element according to the IS theory . However, because the parallel resistance of 60 nm Alq layer is much larger than that of the doped CBP layer in the devices, the RC element of the CBP layer can be treated as only a capacitor.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8] Such high doping concentration limits the application of doping technology in organic semiconductors because the diffusion of dopants can destabilize organic electronic devices. 9,10 In previous papers, we reported that a diverse range of charge generation efficiencies were obtained for various combinations of p-dopants and hosts. 6,7 The charge generation efficiencies of p-dopants depended on the energy difference between the highest occupied molecular orbital ͑HOMO͒ level of the hosts and the lowest unoccupied molecular orbital ͑LUMO͒ level of the dopant ͑⌬E = E HOMO,host − E LUMO,dopant ͒.…”
Section: Homogeneous Dispersion Of Organic P-dopants In An Organic Sementioning
confidence: 99%
“…b) show a capacitance drop at an inflection frequency of about 10 5 Hz. This suggests the presence of a geometric RC time constant effect of series resistance due to lead/contact resistance . In Cell H2, the capacitance before dropping is 8.0 nF, which corresponds to a relative dielectric constant of ε r (CBP) = 3.6 using a parallel‐capacitor model calculation .…”
Section: Resultsmentioning
confidence: 99%
“…This results in decreasing resistivity of partial NPB layer. Chen and coworkers reported that CsF (doped in the MADN layer) diffused into the neighboring Alq 3 layer. The diffusion width exceeds 9 nm.…”
Section: Resultsmentioning
confidence: 99%